Efeito de nanocarreadores de drogas antifúngicas sobre espécies de Candida em biofilmes microcosmos - CALDEIRÃO, Anne Caroline Morais (2021)
Resistance of Candida species to conventional therapies has motivated the development of antifungal nanocarriers based on iron oxide nanoparticles (IONPs) coated with chitosan (CS). This study evaluated the effects of IONPs-CS as carriers of miconazole (MCZ) or fluconazole (FLZ) on microcosm biofilms. Pooled saliva from two healthy volunteers supplemented with Candida albicans and Candida glabrata was the inoculum for biofilm formation. Biofilms were formed for 96 h on coverslips using the Amsterdam Active Attachment model, followed by 24 h treatment with nanocarriers containing different concentrations of each antifungal (78 and 156 µg/mL). MCZ or FLZ (156 µg/mL), and untreated biofilms were considered as controls. Anti-biofilm effects were evaluated by enumeration of colony-forming units (CFUs), composition of the extracellular matrix, lactic acid production, and structure and live/dead biofilm cells (confocal laser scanning microscopy - CLSM). Data were analyzed by 1-way ANOVA and Fisher LSD’s test (α = 0.05). IONPs-CS carrying MCZ or FLZ were the most effective treatments in reducing CFUs compared to either antifungal agent alone for C. albicans and MCZ for C. glabrata. Significant reductions in mutans streptococci and Lactobacillus spp. were shown, though mainly for the MCZ nanocarrier. Antifungals and their nanocarriers also showed significantly higher proportions of dead cells compared to untreated biofilm by CLSM (p < 0.001), and promoted significant reductions in lactic acid, while simultaneously showing increases in some components of the extracellular matrix. These findings reinforce the use of nanocarriers as effective alternatives to fight oral fungal infections.